Folliculitis decalvans – a case study and an overview of literature (Journal of Medical Science, 2018)
Folliculitis decalvans is a rare disease that leads to alopecia. This disease is a major challenge for physicians due to the therapeutic difficulties. This publication describes the case of a patient in whom a dermatological condition had improved after using doxycycline.